Radiation Interception by Lowland Tropical Forest and Productivity of its Three Tree Species - Abdullah, Ahmad Makmom (1997)
The present study was conducted at Pasoh Forest Reserve, located in Negeri Sembilan Malaysia, at about 2°59'N and l02°18'E. The aims of the study were to determine the light environment in the lowland tropical forest and the light interception by the forest canopy and to understand the physiological responses of those selected species to different light in relation to their growth performances. Photon flux densities in different microsites and a clearing within a lowland evergreen tropical forest has been measured and compared between dry and rainy seasons under various of weather conditions. Measurements of PPD were monitored continuously at 5 min intervals over 14-29 day period using quantum sensors under the understorey, small gap, medium gap, big gap and open area. Vertical distribution of PFDs at different height levels of 52 m, 42 m, 33 m, 23 m, 19 m, 14 m, 7 m and on the forest floor were also measured. Daily average PFO, total daily PFO and average daily frequency distribution were analyzed. Daily total PFO in the open area, big gap, medium gap, small gap and understorey sites during the rainy season of November to January 1992 were 51-55, 17.8, 8.1. 8 and 4.51 %, of the daily total PFO recorded in the clearing, respectively. Daily total PFO in the big gap during the dry season was on the average 2 times lower than during the rainy season. In the clearing, high proportion of 5-min average was greater than 500 µmol m-2 S⁻¹, while in the medium, small gaps and understorey, were between 10 and 50 µmol m-l S⁻¹. On diurnal basis, there were high variations in PFO distributions at canopy height of 42 and 52 m during the midday. Mid canopy showed high variations in PFD during the study period. The highest daily total PPO recorded at 52 m was 50 mol m⁻² and the lowest value was found to be at the forest floor. The canopy of the emergent at 33 m height intercepted more than 50% of PFD. In situ growth experiments were carried out by establishing uniform sized seedlings of Shorea leprosula and Neobalanocarpus heimii in each micro site. Diurnal photosynthesis and growth performances were measured accordingly. Open area and big gap sites showed higher growth and photosynthetic rates. Photosynthetic light response curves of S. leprosula and Neobalanocarpus heimii seedlings grown inside the microsites were established. In addition, P-I response curves of N. heimii and Dipterocarpus sublamellatus canopy leaves were also established. The average photosynthetic light response parameters, a, P max, R and e which were calculated based on Thomley model. The a, Pmax, R and Bin canopy leaves of N. heimii and D.